(untitled) (Bangladesh Journal of Plant Taxonomy, 2008)
Not available. Keywords: Aristolochia elegans Mast., New record, Bangladesh Â DOI: 10.3329/bjpt.v15i2.1753 Â Bangladesh J. Plant Taxon. 15(2): 155-158, 2008 (December)